2004
DOI: 10.1111/j.1467-9256.2004.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Performance and Regime Legitimacy in Post-Communist Bulgaria

Abstract: It is commonly assumed that socio‐economic conditions strongly influence political attitudes. Since democratic rule is based on the consent of the ruled, a secure and stable democracy cannot be established and maintained without broad‐based popular endorsement, which is especially important for nascent post‐communist democracies. Painful economic difficulties may engender deep anti‐system sentiments at the mass level, encouraging anti‐regime activism at the elite level. From this perspective, democratic legiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The evidence shows that these dimensions of economic performance influence support for and satisfaction with democracy (Fernandez and Kuenzi, 2010). However, most studies have found that political performance is far more important to democratic consolidation than economic performance is (Bratton and Mattes, 2001; Gilley, 2006; Mishler and Rose, 2001; Vassilev, 2004). Diamond (1999: 192) has summed up the evidence thus: ‘The growing evidence from many countries and regions suggests that, in forming beliefs about regime legitimacy, citizens weigh independently – and much more heavily – the political performance of the system.’ Political performance has been conceptualized in different ways, including respect for civil liberties and political rights, and control of corruption (Anderson and Tverdova, 2003; Bratton and Mattes, 2001; Seligson, 2002).…”
Section: Explaining Support For Democracy: Theoretical Expectationsmentioning
confidence: 99%
“…The evidence shows that these dimensions of economic performance influence support for and satisfaction with democracy (Fernandez and Kuenzi, 2010). However, most studies have found that political performance is far more important to democratic consolidation than economic performance is (Bratton and Mattes, 2001; Gilley, 2006; Mishler and Rose, 2001; Vassilev, 2004). Diamond (1999: 192) has summed up the evidence thus: ‘The growing evidence from many countries and regions suggests that, in forming beliefs about regime legitimacy, citizens weigh independently – and much more heavily – the political performance of the system.’ Political performance has been conceptualized in different ways, including respect for civil liberties and political rights, and control of corruption (Anderson and Tverdova, 2003; Bratton and Mattes, 2001; Seligson, 2002).…”
Section: Explaining Support For Democracy: Theoretical Expectationsmentioning
confidence: 99%
“…Political factors are the second main group of hypothesized sources of state legitimacy. In recent studies, the importance of political factors has been shown to overwhelm the sorts of socioeconomic factors mentioned above (Anderson and Guillory, 1997;Evans and Whitefield, 1995;Lillbacka, 1999;Miller and Listhaug, 1999;Mishler and Rose, 1997, 2001a, 2001bNorris, 1999;Vassilev, 2004). As Diamond summarized: "The growing evidence from many countries and regions suggests that, in forming beliefs about regime legitimacy, citizens weigh independently -and much more heavily -the political performance of the system" (1999: 192).…”
Section: Political Determinantsmentioning
confidence: 99%
“…The goal of the current study is to determine the influence of different social groups on state legitimacy & Listhaug, 1999;Mishler & Rose, 1997, 2001a, 2001b, 2002Norris, 1999;Vassilev, 2004). The literature mentions political factors such as political support, institutional trust, or participation in the public sphere.…”
Section: Introductionmentioning
confidence: 99%